Solve each of the following equation:

 1)\ \    x^2-11x+28=0    

    x^2-7x-4x+28=0    

    x (x-4)-7 (x-4)=0    

    (x-4)(x-7)=0    

    \therefore \ x=4 or  x=7    

\\

 2)\ \   x^2-13x=68    

    x^2-13x-68x=0    

    x^2-17x+4x-68x=0    

    x(x-17)+4(x-17)=0    

    \therefore \ x=17, or x=-4    

\\

 3)\ \   x^2+2x=48    

    x^2+2x-48=0    

    x^2+8x-6x-48=0    

    x(x+8)-6(x+8)=0    

    (x-6)(x+8)=0    

    \therefore \  x=6 or x=-8    

\\

 4)\ \   x^2-2x=3    

    x^2-2x-3=0    

    x^2-3x+1x-3=0    

    (x+1)(x-3)=0    

    x(x-3)+1(x-3)=0    

    x=-1 or x=3    

\\ m42x

 5)\ \   x^2-49=0    

    (x-7)(x+7)=0    

    x=7 or x=-7    

\\

 6)\ \   3x^2-243=0    

    3 (x^2-81)=0    

    (x-9)(x+9)=0    

    x=9 or x=-9    

\\

 7)\ \   16x^2=9    

    16 x^2-9=0    

    (4x-3)(4x+3)=0    

    x=\frac{3}{4}  \ or\  x=\frac{(-3)}{4}    

\\

 8)\ \   3x^2+13x=10    

     3x^2+13x-10=0    

    3x^2-2x+15x-10=0    

    x(3x-2)+5(3x-2)=0    

    (3x-2)(x+5)=0    

    x=\frac{2}{3}  or x=-5    

\\

 9)\ \   2x^2-7x+3=0    

    2 x^2-6x-x+3=0    

    2x(x-3)-1(x-3)=0    

    (2x-1)(x-3)=0    

    x=\frac{1}{2}  or x=3    

\\

 10)\ \   6x^2+5x=6    

    6x^2+5x-6=0    

    6x^2+9x-4x-6=0    

    3x(2x+3)-2(2x+3)=0    

    (3x-2)(2x+3)=0    

    x=\frac{2}{3}  or x=\frac{(-3)}{2}    

\\

  11)\ \   10x^2+11x+3=0    

    10x^2+6x+5x+3=0    

    5x(2x+1)+3(2x+1)=0    

    (2x+1)(5x+3)=0    

    x=\frac{(-1)}{2}  or x=\frac{(-3)}{5}    

\\

12)\ \     9x^2+8=22x    

    9x^2-22x+8=0    

    9x^2-18x-4x+8=0     

    9x(x-2)-4(x-2)=0    

    (x-2)(9x-4)=0    

    x=2  or x=\frac{4}{9}    

\\

 13)\ \   22x^2+x=6    

    22x^2+x-6=0    

    22x^2+11x-12x-6=0    

    11x(2x+1)-6(2x+1)=0    

    (2x+1)(11x-6)=0    

    x=\frac{(-1)}{2} or  x=\frac{6}{11}  

\\

14)\ \     2x^2+5x-7=0    

    2x^2+7x-2x-7=0    

    2x(x-1))+7(x-1)=0    

    (x-1)(2x+7)=0    

    x=1  or x=\frac{(-7)}{2}    

\\ m43x

 15)\ \   6y^2=7y+20    

     6y^2-7y-20=0    

    6y^2-15y+8y-20=0    

    3y(2y-5)+4(2y-5)=0    

    (2y-5)(3y+4)=0    

y=\frac{5}{2} \ or \ y=\frac{(-4)}{3}

\\

 16)\ \   4z^2=11z+3    

    4z^2-11z-3=0    

    4z^2+z-12x-3=0    

    4z(z-3)+(z-3)=0    

    (z-3)(4z+1)=0    

    z=3 or z=\frac{(-1)}{4}  

\\

 17)\ \    (t-2)^2=36    

    t^2+4-4t=36    

    t^2-4t-32=0    

    t^2-8t+4t-32=0    

    t(t+4)-8(t+4)=0    

    (t+4)(t-8)=0    

    t=-4   or  t=8    

\\

18)\ \     (2x+3)(x-4)=6    

    2x^2+3x-8x-12=6    

    2x^2-5x-18=0    

    2x^2-9x+4x-18=0    

    2x(x+2)-9(x+2)=0    

    2x (x+2)(2x-9)=0    

    x=-2 or x=\frac{9}{2}    

\\

  19)\ \    12x+7=10/x    

    12x^2+7x-10=0    

    12x^2+15x-8x-10=0    

    4x(3x-2)+5(3x-2)=0    

    (3x-2)(4x+5)=0    

    x=\frac{2}{3}  \ or \ x=\frac{(-5)}{4}    

\\

 20)\ \     x^2-10x+21=0    

    x^2-7x-3x+21=0    

    x(x-7)-3(x-7)=0    

    (x-7)(x-3)=0    

    x=7 \ or \ x=3    

\\

 21)\ \    \frac{x}{3}-\frac{6}{x}=1    

    x^2-18=3x    

    x^2-3x-18=0    

    x^2-6x+3x-18=0    

    x(x+3)-6(x+3)    

    (x+3)(x-6)=0    

    x=-3 \ or\  x=6    

\\

 22)\ \    \frac{(x+1)}{(x+5)}=\frac{(2x-3)}{(x+3)}    

    x^2+x+3x+3=2x^2-3x+10x-15    

    x^2+3x-18=0    

    x^2+6x-3x-18=0    

    x(x-3)+6(x-3)=0    

    (x-3)(x+6)    

    x=3 or x=-6    

\\

  23)\ \    \frac{(x+1)}{(3x-7)}=\frac{(x-1)}{(2x-5)}    

    2x^2+2x-5x-5=3x^2-3x-7x+7    

    2x^2-3x-5=3x^2-10x+7    

    x^2-7x+12=0    

    x^2-3x-4x+12=0    

    x(x-3)-4(x-3)=0    

    (x-3)(x-4)=0    

    x=3 or x=4    

\\

 24)\ \    \frac{1}{(x-1)}-\frac{1}{(x+2)}=\frac{3}{4}    

    (x+2)-(x-1)=\frac{3}{4} (x-1)(x+2)    

    3=\frac{3}{4}  (x^2-x+2x-2)    

    4=x^2+x-2    

    x^2+x-6=0    

    x^2+3x-2x-6=0    

    x(x-2)+3(x-2)=0    

    (x-2)(x+3)=0    

    x=2 \ or\  x=-3    

\\

 25)\ \   \frac{4}{(x-1)}-\frac{3}{x}=\frac{5}{x+2}   

Multiply LHS and RHS  by     (x-1)(x)(x+2)    

    4(x)(x+2)-3(x-1)(x+2)=5(x-1)(x)    

    4x^2+8x-3x^2-3x+6=5x^2-5x    

    4x^2+8x-3x^2-3x+6=5x^2-5x    

    x^2+5x+6=5x^2-5x    

    4x^2-10x-6=0    

    2x^2-5x-3=0    

    2x^2-6x+x-3=0    

    2x (x-3)+(x-3)=1    

    (x-3)(2x+1)=0    

    x=3 or-\frac{1}{2}    

\\ m44x

 26)\ \  \frac{x+2)}{(x-1)}- \frac{4-x}{2x} = \frac{7}{2}    

    2x(x+2)-(x-1)(4-x)=\frac{7}{2}(x-1)(2x)    

    2x^2+4x-4x+4+x^2-x=7(x^2-x)    

    3x^2-x+4=7x^2-7x    

    4x^2-6x-4=0    

    2x^2-3x-2=0    

    2x^2-4x+x-2=0    

    2x (x-2)+1(x-2)=0    

    (x-2)(2x+1)=0    

    x=2  or x=-\frac{1}{2}    

Advertisements